Reporting Guidelines for the Early-Phase Clinical Evaluation of Applications Using Extended Reality: RATE-XR Qualitative Study Guideline - Johan H Vlake; Denzel LQ Drop; Jasper Van Bommel; Giuseppe Riva; Brenda K Wiederhold; Pietro Cipresso; Albert S Rizzo; Barbara O Rothbaum; Cristina Botella; Lotty Hooft; Oscar J Bienvenu; Christian Jung; et al. (JMIR Publications, 2024)
BackgroundExtended reality (XR), encompassing technologies such as virtual reality, augmented reality, and mixed reality, has rapidly gained prominence in health care. However, existing XR research often lacks rigor, proper controls, and standardization. ObjectiveTo address this and to enhance the transparency and quality of reporting in early-phase clinical evaluations of XR applications, we present the "Reporting for the early-phase clinical evaluation of applications using extended reality" (RATE-XR) guideline. MethodsWe conducted a 2-round modified Delphi process involving experts from diverse stakeholder categories, and the RATE-XR is therefore the result of a consensus-based, multistakeholder effort. ResultsThe guideline comprises 17 XR-specific (composed of 18 subitems) and 14 generic reporting items, each with a complementary Explanation & Elaboration section. ConclusionsThe items encompass critical aspects of XR research, from clinical utility and safety to human factors and ethics. By offering a comprehensive checklist for reporting, the RATE-XR guideline facilitates robust assessment and replication of early-stage clinical XR studies. It underscores the need for transparency, patient-centeredness, and balanced evaluation of the applications of XR in health care. By providing an actionable checklist of minimal reporting items, this guideline will facilitate the responsible development and integration of XR technologies into health care and related fields.